Textural Effects on Perceived Satiation and Ad Libitum Intake of Potato Chips in Males and Females - Jimmy Cahayadi; Sze Ying Leong; Indrawati Oey; Mei Peng (Foods, 2020)
Food texture plays a critical role in influencing an individual’s perceived satiation and ad libitum intake. It remains unclear, however, whether such textural changes can also affect snack consumption. This study aimed to address this question by testing for changes in perceived satiation and ad libitum intake of two types of potato chips with varying hardness. In addition, the observed effect was compared across gender groups. With a crossover design, 74 participants (31 females and 43 males) performed a food consumption task for two types of chips produced from potatoes that were either untreated or treated with pulsed electric fields (PEF) technology. Sensory analyses indicated that these two types of chips had comparable hedonic value, despite a clear textural difference. Across sexes, the results revealed a significant difference in perceived satiation for the two types of chips (p = 0.009), but not in intake. By contrast, analyses of males alone revealed that male participants rated PEF-treated chips to be more satiating than the control chips and correspondingly consumed less (p < 0.05). Overall, findings from the study suggest that modifications of food texture can be a helpful tool in reducing energy intake from snack consumption. The contrasting results from different gender groups highlight the importance of considering gender effects in studies of eating behaviour.